2015
DOI: 10.4093/dmj.2015.39.4.328
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Fat Oxidation Rate during Exercise in Korean Women with Type 2 Diabetes Mellitus

Abstract: BackgroundThe purpose of this study was to determine the appropriate exercise intensity associated with maximum fat oxidation, improvement of body composition, and metabolic status in Korean women with type 2 diabetes mellitus (T2DM).MethodsThe study included a T2DM group (12 women) and a control group (12 women). The groups were matched in age and body mass index. The subjects performed a graded exercise test on a cycle ergometer to measure their maximal fat oxidation (Fatmax). We also measured their body com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…FATmax is a low-to-moderate exercise intensity. The average FATmax intensity has been reported at 34 %VO 2 max in middle-aged women (58 ± 7 yrs) with type 2 diabetes [47]; while a recent study has found that overweight middle-aged women (51 ± 6 yrs) reached their FATmax at 52 %VO 2 max [48]. Some studies have applied FATmax exercise training to adults with metabolic diseases [6,7,15,48,49,52], with reported outcomes that include decreased body fat [48,49] and improved insulin sensitivity [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…FATmax is a low-to-moderate exercise intensity. The average FATmax intensity has been reported at 34 %VO 2 max in middle-aged women (58 ± 7 yrs) with type 2 diabetes [47]; while a recent study has found that overweight middle-aged women (51 ± 6 yrs) reached their FATmax at 52 %VO 2 max [48]. Some studies have applied FATmax exercise training to adults with metabolic diseases [6,7,15,48,49,52], with reported outcomes that include decreased body fat [48,49] and improved insulin sensitivity [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, patients with T2D demonstrated a lower lipid oxidation rate per fat-free mass at all five relative exercise intensities that were assessed in that study (i.e., 20, 30, 40, 50 and 60% of the peak work rate) [ 104 ]. Another indication of an impaired capacity for lipid oxidation for patients with T2D comes from Suk et al, who compared women with T2D with age-, sex- and BMI-matched controls and found that T2D was associated with a lower fatmax (~ 34 v. ~ 52% of V̇O 2max ) and lipid oxidation rate at fatmax (~ 0.38 v. ~ 0.55 g·min − 1 ) [ 105 ]. Specifically, the rate of lipid oxidation was lower at three of the five relative intensities that were investigated (40, 50 and 60 of V̇O 2max , but not 20 or 30%) [ 105 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another indication of an impaired capacity for lipid oxidation for patients with T2D comes from Suk et al, who compared women with T2D with age-, sex- and BMI-matched controls and found that T2D was associated with a lower fatmax (~ 34 v. ~ 52% of V̇O 2max ) and lipid oxidation rate at fatmax (~ 0.38 v. ~ 0.55 g·min − 1 ) [ 105 ]. Specifically, the rate of lipid oxidation was lower at three of the five relative intensities that were investigated (40, 50 and 60 of V̇O 2max , but not 20 or 30%) [ 105 ]. Conversely, Mogensen et al compared patients with T2D to age-, BMI- and PA-matched FH- controls with normal glucose tolerance and found that both the maximal rate of lipid oxidation (~ 0.3 g·min − 1 ) and fatmax (~ 40% V̇O 2max ) were not different between groups [ 106 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study participants were untrained young Saudi men, and their maximal fat oxidation was low, comparable with previously published sedentary, type 2 diabetes, and obese groups. For example, the maximal fat oxidation during FR and DHR in this study was close to or comparable with women with type 2 diabetes (0.38 g/min), and fat oxidation during FR and DHR was lower than untrained healthy women (0.54 g/min) [ 19 ]. The same outcomes were found in obese young men (0.38 ± 0.13 g/min) while fat oxidation in the active was 0.58 ± 0.07 g/min [ 20 ].…”
Section: Discussionmentioning
confidence: 67%
“…For example, the –12% gradient used in the present study could increase cardiovascular and metabolic demands and muscle damage to a greater extent than gentler inclinations, such as between –5% and –10% [ 28 ]. Moreover, several factors such as insulin level [ 19 ], mode of exercise [ 29 ], and the recruitment of muscle mass during the test [ 30 ] influence the rate of exercise-induced fat oxidation. For example, when individuals performed cycling and rowing exercises at the same intensity, fat oxidation was greater during the rowing session, and this was likely due to the larger muscle mass recruited during rowing [ 30 ].…”
Section: Discussionmentioning
confidence: 99%